Impact of chicken proteins on canine preference as measured using sensory analysis - Shields, Chelsie Jo (Kansas State University, 2022)
As the number of households with pets in the US continues to grow, so does the amount of pet food produced by the industry. It is important to understand the impact of feeding all these pets on our environment. Sustainability, defined from a pet food industry standpoint, is described as the ability to produce enough food for the growing pet population, while providing sufficient nutrition, and leaving the smallest environmental footprint possible. Among the rising number of pets within each household, dogs are the most popular. To provide a sustainable future, the shift to more sustainable ingredients must be discussed. Of the macronutrients needed to formulate a complete extruded canine food, protein is essential but is also the most expensive. Chicken has been shown to have the lowest impact from a carbon footprint standpoint, yet consumers have a negative perspective when it comes to any other form of chicken besides fresh chicken in their pet’s food. However, chicken by-products and meals provide a quality source of dietary protein, vitamins, and minerals to create nutritionally complete dog food products. The first objective of this research was to formulate nutritionally adequate extruded dog foods utilizing four different chicken proteins as the sole animal protein source and to determine canine preference. Palatability was measured using the two-bowl test to determine if a preference between the different chicken proteins was recognized. All five experimental formulas were tested with a panel of 25 dogs for each palatability test and took place over 2 days. There was a preference (p<0.05) for the chicken by-product meal formula over the fresh chicken at 14%, fresh chicken at 25%, and dried chicken formulas. There was no preference when the chicken by-product meal formula was compared to the chicken meal formula. The second objective was to understand the sensory characteristics of the canine formulas through descriptive sensory analysis and consumer acceptance. The descriptive sensory attributes for aroma and appearance between the experimental formulas were similar. Consumer data showed that the chicken by-product meal formula was the most liked in aroma, appearance and overall liking and was ranked the most preferred when measured blindly. Consumers were then provided the chicken protein ingredients for each sample and were asked to rank them again. Once consumers were made aware of the protein sources for each sample, their ranking changed to prefer the fresh chicken samples. The last objective was to determine volatile compounds present in each of the experimental formulas and to identify possible correlations to the sensory aroma attributes. The qualitative analysis tentatively identified thirteen compounds in each of the samples, consisting mostly of carboxylic acids and aldehydes. Partial Least Squares regression found some correlations between sensory aroma attributes and volatile compounds. Hexanal, heptanoic acid, 2-heptanone, and octanoic acid correlated closest to the oxidized oil aroma attribute while acetic acid, propanoic acid, and butanoic acid correlated closest to the liver aroma attribute. This research will provide insight on canine palatability of fresh chicken, dried chicken, chicken meal, and chicken by-product meal as the main animal protein source in extruded dog foods. It will also describe the sensory characteristics associated with the different chicken protein sources used, consumers’ acceptance, and correlations to volatile compounds that may associate to sensory aroma attributes and possibly canine preference.
Keywords: Dog food; Palatability; Sensory analysis; Volatile compounds